The Coexistence of Oryctes rhinoceros L. and Xylotrupes gideon L. (Coleoptera: Scarabaeidae) on Immature Plant in Oil Palm Plantation - Anugerah Pustakawan Pradipta; F. X. Wagiman; Witjaksono Witjaksono (Universitas Gadjah Mada, 2020)
Oryctes rhinoceros L. and Xylotrupes gideon L. (Coleoptera: Scarabaeidae) are known to attack palms. O. rhinoceros is a major pest in oil palm while X. gideon is a minor pest found in certain areas with a relatively few numbers. Collecting these beetles by hand picking and trapping are intended to reduce their population. Objectives of this study were to describe an intimacy of shared existence of O. rhinoceros and X. gideon in the oil palm plantation, and to determine the effect of manual collection of the beetles from the decomposing trunks compared to those that were collected using attractant traps. The study was conducted in Asahan Regency, North Sumatera, in Sei Silau PTPN III oil palm plantation. Five traps (2 Ha/trap) containing the pheromone ethyl-4-methyloctanoate were installed randomly at a replanting area of immature palm. Beetle collection was performed daily for 30 consecutive days using two methods, i.e. (a) hand-picking of beetles on the decomposed trunks at surrounding the trap for 2 hour per day, and (b) using pheromone traps. Simple regression and correlation model was used for data analysis. Results showed that coexistence of O. rhinoceros and X. gideon was observed at the breeding sites of decomposing trunks, but not in the traps, and their coexistence showed a weak relationship (r = 0.12). Number of collected O. rhinoceros (221 beetles) was much more than X. gideon (82 beetles). Natural sex ratio (male: female) was approximately 0.5 for O. rhinoceros and 0.4 for X. gideon. Collection of the beetles in the decomposed trunks showed a moderately positive relationship (r = 0.43) with, and significantly influenced (18.73%) to the collection of beetles using pheromone traps.